Comparative Analysis of Arsenic Detection in Water by Field Test Kit and AAS Methods - Das3; D.A. Chowdhury4, B. Sarkar1*, A.H.M. Solaiman2, A. K. (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Methods for detection of arsenic in water samples from ground water under field conditions have been studied. A comparative analysis based on experimental determination of arsenic in large number of water samples by Test Kits (Gutzeit Method) and by atomic absorption spectrophotometry (AAS) has been made. It is observed that when the actual concentration of arsenic in water is below 100 ppb, the result of measurement by test kit is lower than that obtained by AAS. On the other hand, higher values of arsenic concentration are given by test kit, when the actual concentration is over 100 ppb. In general, the result obtained by test kit is found to differ by 20 - 50 % from that obtained by sensitive laboratory method AAS.